Tensile, thermal and water absorption properties of corn stalk filled low density polyethylene composites: effect of coconut oil coupling agent - Salmah Husseinsyah; Koay, Seong Chun; Chan, Ming Yeng; Azimah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2016)
In this study, the corn stalk (CS) had been utilized as natural filler in low density polyethylene (LDPE). The effect of CS loading and coconut oil coupling agent (COCA) on tensile, thermal and water absorption properties of LDPE/CS composites were investigated. The increases of CS decreased the tensile strength and elongation at break of LDPE/CS composites, but increased in Young’s modulus. The incorporation of CS also contributed to high water uptake of LDPE/CS composites. However, the presence of CS has increased the crystallinity of composites and LDPE matrix due to nucleating effect. The addition of COCA has significantly increased the tensile strength, elongation at break, water resistivity and crystallinity of LDPE/CS composites, but slightly reduced in Young’s modulus. The scanning electron microscope (SEM) also evidence the presence of COCA improved the adhesion between CS and LDPE matrix.